ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PERILAKU MORAL KEAGAMAAN MAHASISWA - Magdalena, Magdalena (Institut Agama Islam Negeri Padangsidimpuan, 2018)
This study aimed to determine influenced factors of the studentsâ gender, organization participant, and education background, and to Islamic moral action. Based the data analysis, there are many findings. There was a correlation between studentsâ gender, organization participant, and education background simultanly to Islamic moral action. Then, there was a different Islamic moral action based on the gender, organization participant, and education background